PENGARUH IKLIM ORGANISASI DAN LINGKUNGAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA HOTEL BATAM VIEW KOTA BATAM - Wahyudi, Alwi; ', Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to find out whether the organizational climate has an effect on employee morale, to find out whether the work environment has an effect on work morale, and to find out whether the organizational climate and work environment have an effect on work morale. The research method used is a quantitative method and uses secondary and primary data. Primary data was obtained from respondents who were collected through a questionnaire consisting of 24 statements. The sample consisted of 42 respondents who were all employees at the Batam View Hotel. The measurement scale uses a Likert scale. Data analysis includes: validity test, reliability test, simple linear regression test, multiple linear regression test, t test, f test, and coefficient of determination test. This research data analysis technique uses SPSS. The results of this research show, (1) There is a significant influence of organizational climate on employee morale at the Batam View Hotel, (2) There is a significant influence of the work environment on employee morale at the Batam View Hotel, and (3) There is a significant influence of organizational climate and work environment on employee morale at the Batam View Hotel. Keywords: organizational climate; work environment; employee morale